Glioblastoma in the Canton of Zurich, Switzerland revisited: 2005 to 2009. Issue 14 (18th April 2016) - Gramatzki, Dorothee; Dehler, Silvia; Rushing, Elisabeth Jane; Zaugg, Kathrin; Hofer, Silvia; Yonekawa, Yasuhiro; Bertalanffy, Helmut; Valavanis, Anton; Korol, Dimitri; Rohrmann, Sabine; Pless, Miklos; Oberle, Joachim; et al.
Abstract : BACKGROUND: A population‐based analysis of patients with glioma diagnosed between 1980 and 1994 in the Canton of Zurich in Switzerland confirmed the overall poor prognosis of glioblastoma. To explore changes in outcome, registry data were reevaluated for patients diagnosed between 2005 and 2009. METHODS: Patients with glioblastoma who were diagnosed between 2005 and 2009 were identified by the Zurich and Zug Cancer Registry. The prognostic significance of epidemiological and clinical data, isocitrate dehydrogenase 1 (IDH1) R132H mutation status, and O6 methylguanine DNA methyltransferase ( MGMT ) promoter methylation status was analyzed using the Kaplan‐Meier method and the Cox proportional hazards model. RESULTS: A total of 264 patients with glioblastoma were identified, for an annual incidence of 3.9 compared with the previous incidence of 3.7. The mean age of the patients at the time of diagnosis was 59.5 years in the current cohort compared with 61.3 years previously. The overall survival (OS) rate was 46.4% at 1 year, 22.5% at 2 years, and 14.4% at 3 years in the current study compared with 17.7% at 1 year, 3.3% at 2 years, and 1.2% at 3 years as reported previously. The median OS for all patients with glioblastoma was 11.5 months compared with 4.9 months in the former patient population. The median OS was 1.9 months for best supportive care, 6.2 months for radiotherapy alone, 6.7 months for temozolomide alone, and 17.0 months for radiotherapy plus temozolomide. Multivariate analysis revealed age, Karnofsky performance score, extent of tumor resection, first‐line treatment, year of diagnosis, and MGMT promoter methylation status were associated with survival in patients with IDH1 R132H ‐nonmutant glioblastoma. CONCLUSIONS: The OS of patients newly diagnosed with glioblastoma in the Canton of Zurich in Switzerland markedly improved from 1980 through 1994 to 2005 through 2009. Cancer 2016;122:2206–15 . © 2016 American Cancer Society . Abstract : Population‐based studies of glioblastoma are scarce and traditionally have suffered from methodological limitations. In the current study, the authors demonstrate that, on a population level, the overall survival of patients with glioblastoma diagnosed in the Canton of Zurich in Switzerland has markedly improved from the pre‐temozolomide to the temozolomide era. Age, Karnofsky performance score, extent of tumor resection, first‐line treatment regimens, and, as demonstrated for the first time, MGMT promoter methylation status as well as isocitrate dehydrogenase 1 R132H mutation status are associated with survival today.